Supplementation of Feed Grade Sodium Bisulfate in Broiler Diets Improves Feed Efficiency - Ruiz-Feria, C.A.; Larrison, E.; Davis, M.; Farnell, M.; Carey, J.; Grimes, J.L.; Pitts, J. (International Journal of Poultry Science, 2011)
The effects of Sodium Bisulfate (SB) supplementation on growth, intestinal integrity, blood gas chemistry and litter microbiology of broiler chickens were evaluated. Birds were fed a corn-soybean meal diet meeting all of the NRC (1994) requirements. In Exp. 1 birds were fed diets supplemented with 0 (control diet, CTL), 0.25, 0.5, or 0.75% (w/w) of feed-grade SB (SB25, SB50 and SB75, respectively); in Exp. 2 and 3 only the CTL, SB25 and SB75 diets were evaluated. In Exp. 4 the chicks (n = 920) were placed in 20 pens and fed the CTL diet, or the SB25 diet offered during the first 21, 35, or 49 d (21D, 35D and 49D, respectively); the CTL diet was offered until the end of experiment (d 49) for treatments 21D and 35D. The data was analyzed as a two way ANOVA (diet and gender as main effects). In Exp. 1 birds fed diets with SB had lower FC than birds fed the CTL diet, but BW was not different among treatments. In Exp. 2 females fed the SB25 diet were heavier (p